1986
DOI: 10.1099/00222615-22-2-143
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal, Bacteriolytic and Opsonic Activity of Human Serum Against Escherichia Coli

Abstract: Summary. The effect of human serum on Escherichia coli was studied with serumsensitive and serum-resistant strains. The bactericidal effect of human serum on serumsensitive strains of E. coli depended on the activation of the classical complement pathway. The role of activation of the alternative pathway was less important. After incubation in sub-bactericidal concentrations of serum these strains were also easily phagocytosed by polymorphonuclear leukocytes (PMNL). Strains of E. coli of certain 0-types requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The results of our study confirm those reported previously that unencapsulated strains incubated in low concentrations of serum are easily ingested by granulocytes (8,19,21), whereas encapsulated strains are not effectively opsonized in serum. Extracellular polysaccharide may play an important role in the protection of bacteria against serum opsonic activity (1,3,16,20).…”
Section: Discussionsupporting
confidence: 82%
“…The results of our study confirm those reported previously that unencapsulated strains incubated in low concentrations of serum are easily ingested by granulocytes (8,19,21), whereas encapsulated strains are not effectively opsonized in serum. Extracellular polysaccharide may play an important role in the protection of bacteria against serum opsonic activity (1,3,16,20).…”
Section: Discussionsupporting
confidence: 82%
“…Bacteriolytic effect of the antimicrobial agent is detectable only by assessing the decrease in the OD signal [31–33]. The OD detection limit of the used plate reader, for the bacterial suspension, was approximately 1 × 10 6 cells/well corresponding to 0.030 OD in 200  μ L, and therefore 10-fold higher bacterial cell number (3 × 10 6 cells/well) had to be used in killing experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The complement system is an important defence mechanism against various invading pathogens [25]. However, the sensitivity to the bactericidal action of complement varies considerably according to the structural determinants of different bacterial strains [25, 26]. In general, gram‐positive bacteria are relatively resistant to the bacteriolytic activity of complement, probably because their peptidoglycan layer is too thick for the complement‐derived membrane attack complex to penetrate [27, 28].…”
Section: Discussionmentioning
confidence: 99%